2019
DOI: 10.2174/1570178615666181022145338
|View full text |Cite
|
Sign up to set email alerts
|

Cu-Fe Spinels: First Heterogeneous and Magnetically Recoverable Catalyst for the Ferrier Rearrangement of 2-Nitroglycals

Abstract: Cu-Fe spinels promoted the Ferrier rearrangement of 2-nitroglycals with several O-nucleophiles. 2,3-Unsaturated carbohydrate derivatives were prepared by the reaction of 3,4,6-tri-Oacetyl- 2-nitroglucal and alcohols in the presence of 5 % of CuFe2O4. After separation of the catalyst with an external magnet, the reaction products were obtained in good yields and high stereo and regioselectivity. Also, S- and heterocyclic C-3 substituted 2-nitro-endo-glycals could be prepared by this method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…((2R,3S,6S)‐3‐acetoxy‐6‐isopropoxy‐5‐nitro‐3,6‐dihydro‐2H‐pyran‐2‐yl)methyl acetate (3 r) : [14a] Colorless syrup. 1 H NMR (500 MHz, CDCl 3 ) δ 7.15 (d, J =2.2 Hz, 1H), 5.66 (s, 1H), 5.55 (dd, J =9.3, 1.8 Hz, 1H), 4.31–4.27 (m, 1H), 4.27–4.23 (m, 2H), 4.07 (m, J =6.2 Hz, 1H), 2.14 (s, 3H), 2.10 (s, 3H), 1.25 (dd, J =14.6, 6.2 Hz, 6H).…”
Section: Methodsmentioning
confidence: 99%
“…((2R,3S,6S)‐3‐acetoxy‐6‐isopropoxy‐5‐nitro‐3,6‐dihydro‐2H‐pyran‐2‐yl)methyl acetate (3 r) : [14a] Colorless syrup. 1 H NMR (500 MHz, CDCl 3 ) δ 7.15 (d, J =2.2 Hz, 1H), 5.66 (s, 1H), 5.55 (dd, J =9.3, 1.8 Hz, 1H), 4.31–4.27 (m, 1H), 4.27–4.23 (m, 2H), 4.07 (m, J =6.2 Hz, 1H), 2.14 (s, 3H), 2.10 (s, 3H), 1.25 (dd, J =14.6, 6.2 Hz, 6H).…”
Section: Methodsmentioning
confidence: 99%
“…The structure and stereochemistry of the rearrangement products were elucidated by NMR and mass spectroscopy and were subsequently compared with the reported data ( Dharuman et al, 2013 ; Lafuente et al, 2019 ; Jiang et al, 2021 ). It was noteworthy that the stereoselectivity of 2-nitro-2,3-unsaturated glycoside compounds was confirmed as α: β > 19:1 by 1 H NMR.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the experimental results and literature studies, a reaction mechanism may be proposed as follows ( Figure 3 ). ( Dharuman et al, 2013 ; Lafuente et al, 2019 ; Jiang et al, 2020b ; Jiang et al, 2021 ): As we know, a halogen substituent at the C-2 position of the glycals has a remarkable effect, and those electron-withdrawing groups would reduce the electron density of the oxocarbenium intermediate, which is commonly assumed as the intermediate cation in the Ferrier rearrangement ( Dong et al, 2019 ). Thus, under the nanocatalysis of Fe 3 O 4 @C@Fe(III), C3 site deacylation in 2-nitro-glucal would occur very slowly and electron transfer would occur in a different way, with the aid of the nucleophiles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with benzylated 2-nitroglycals, acetylated analogues are easier to prepare from corresponding oligosaccharides in two steps, , and the acetyl group, after the reaction, can be readily removed under mild conditions. However, due to its potentially high reactivity, especially the side reaction of Ferrier rearrangement under conventional glycosylation conditions, , the application of acetylated 2-nitroglycals in carbohydrate chemistry is much less developed. In 2013, by using DMAP as a catalyst, Vankar’s group found that acetylated 2-nitroglycals can undergo selective functionalization at the C1- or C3-position based on the properties of nucleophiles.…”
Section: Introductionmentioning
confidence: 99%